PROBIOTICS AS NUTRIENT SUPPLEMENT IN ARTIFICIAL FEED OF GOLD FISH (CARASSIUS AURATUS) - Sinha, Archana; Ghosh, Shubhadeep; Singh, Dharmender (Journal of Indian Fisheries Association, 2015)
The efficacy of three feeds incorporated with different probiotics -Lactobacil, Vizylac and Cyfolac as nutrient supplement was evaluated in anornamental fish, Carassius auratus (Linn.). The basal diet (40% protein) wasprepared and the probiotics were incorporated at different levels viz.Lactobacil at 8 x 107/100g and 12 x 107/100g, Vizylac at 8 x 107/100g and 12 x 107/100g and Cyfolac at 12 x 107/100g. Feeding trial was conducted for a period of4 weeks. At the end of the experiment, bio-growth parameters and proximatecomposition of the fishes were studied. The growth, survival and proteincontent were improved in all the probiotic fed fishes compared to control.The maximum growth (0.74 g) and survival (85%) were observed in fishes fedwith Lactobacil at 12 x 107/100g. It emphasizes that supplementation of feedwith probiotics has a positive impact on the growth, survival and the bodycomposition of goldfish.Keywords: Gold fish, probiotics, nutrient supplement